Pengaruh Cara Aplikasi Pasta Gigi Herbal terhadap Produksi Volatile Sulfur Compound - S. Suryono (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Effect of Herbal Toothpaste Application Method on Production of Volatile Sulfur Compound. Volatile sulfur compound (VSC) is a component of the gas produced by bacteria in the oral cavity, consisting of hydrogen sulfide,methyl mercaptan and dimethyl sulfide. This gas is often used as an indicator to assess the status of bad breath. Herbalbased dental paste has been reported in previous studies to inhibit the growth of germs that cause periodontal disease. Plaque Bacteria in the oral cavity can be reduced by tooth brushing and/or the use of antiseptic material. Two groups of subjects chosen were given treatment using herbal toothpaste in different ways: the first group was by brushing teeth with herbal toothpaste the way they usually do it and the second group was given the treatment by applying herbal paste in the left and right molar region of maxilla. The sampling was performed before treatment, 5 minutes and 2 hours after brushing teeth or applying herbal paste. The result of the experiment indicates that the use of herbal toothpaste with toothbrush and applying method has the same pattern on each component of the sulfur gas that is an increase after five minutes post-application and then a decrease after 2 hours post-application. Herbal toothpaste which is applied by means of brushing or by applying to the teeth affected the levels of VSC components; the level of Hydrogen sulfide decreased, the level of methyl mercaptan was relatively stable, and the level of dimethyl sulfide increased. Herbal toothpaste can be used in a common brushing way or by applying it to the teeth to reduce the levels of VSC gases, especially Hydrogen sulfide in normal subjects.